Ullmann's Encyclopedia of Industrial Chemistry 2000
DOI: 10.1002/14356007.a28_305
|View full text |Cite
|
Sign up to set email alerts
|

Wood

Abstract: The article contains sections titled: 1. Morphology and Properties 1.1. Introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…These are typically richer in extractives and ash and leaner in lignin, compared to woody biomass. 27,28 In view of the literature results and this work, it can be concluded that lignin inhibits the hydrogenation function but is not the key inhibitor on the EG yield.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…These are typically richer in extractives and ash and leaner in lignin, compared to woody biomass. 27,28 In view of the literature results and this work, it can be concluded that lignin inhibits the hydrogenation function but is not the key inhibitor on the EG yield.…”
Section: Resultsmentioning
confidence: 56%
“…Beyond the study by Li et al, all other studies share the choice for a herbaceous type biomass (Miscanthus, barley straw, Jerusalem artichoke, corn stalk). These are typically richer in extractives and ash and leaner in lignin, compared to woody biomass. , In view of the literature results and this work, it can be concluded that lignin inhibits the hydrogenation function but is not the key inhibitor on the EG yield.…”
Section: Resultsmentioning
confidence: 60%
“…Lignin, a natural biopolymer, is a renewable raw material , and constitutes up to 30% of the weight and 40% of the heating value of lignocellulosic biomass . It is produced in large quantities (50 million tons on an annual production, of which only 2% for commercial use) as a byproduct of the pulping industry (Kraft process or organosolv route mainly using EtOH as a solvent) and during the pretreatment processes in cellulosic ethanol plants for bioethanol manufacture. It remains soluble in the strongly alkaline black liquor and is mainly burned for recovery of inorganic chemicals (Na and S), heat, and power generation.…”
Section: Introductionmentioning
confidence: 99%
“…tungstate poisons), such as calcium and magnesium, from the biomass. Carbonates and oxalates of calcium and magnesium, which are typically present in lignocellulosic biomass, 22 are poorly soluble in water (e.g. K sp CaCO 3 (Calcite) = 10 -8.5 mol L −2 , from Al Omari et al), 23 Dissolution of these species can be achieved by acidifying the solution.…”
Section: Process Conceptmentioning
confidence: 99%